Historical biogeography of Temnocephalida (Platyhelminthes, Rhabdocoela): testing the Gondwanan hypothesis. Issue 4 (4th July 2017) - Martínez-Aquino, Andres; Vigliano-relva, Julieta; Brusa, Francisco; Damborenea, Cristina
Abstract : Temnocephalida, a group of small epibiontic worms strictly associated with freshwater hosts, includes 179 taxa in 23 genera, classified in two major groups: Scutarielloidea, distributed in the Palaearctic region, and Temnocephaloidea distributed mainly in the Australian and Neotropical regions. Based on a large-scale spatio-temporal dimension, a biogeographic hypothesis on a Gondwanan scenario was tested. The objective of this study was to describe the geographic distribution patterns of Temnocephalida in a primary biogeographic homology context. A dataset of 793 temnocephalan records, distributed in 45 hydrological basins, and assigned to different hierarchical taxonomic levels was used to construct five presence/absence matrices. We analysed the matrices using Parsimony Analysis of Endemicity (PAE) and Cladistic Analysis of Distributions and Endemism (CADE). Furthermore, we constructed generalized tracks based on area clades with phylogenetic support, i.e., two or more synapomorphies. Six generalized tracks were revealed: a general clade for Eurasia, plus a complex of four hybrid zones with monophyletic relationships included in a major clade with Gondwanan affinities. The results represent the first study using biogeographic analysis to disentangle the distributional patterns of temnocephalids around the world. Based on the integration of the results obtained by biogeographic pattern-based methods, we infer that the fragmentation of Gondwana affected the diversification patterns and distribution of Temnocephalida.